PROFIL MASALAH EMOSIONAL PESERTA DIDIK BERPRESTASI AKADEMIK DENGAN TEMAN SEBAYA (STUDI KUALITATIF PADA PESERTA DIDIK DI SMAN 2 PASAMAN) - Gusrayani, Gusrayani; Nita, Rahma Wira; Putra, Fuddillah (STKIP Pesisir Selatan, 2025)
This research is motivated by the emotional problems experienced by students with academic achievements in interacting with peers at SMAN 2 Pasaman. This problem is important to examine because difficulties in understanding oneself can affect the quality of social relationships and communication between students. This study aims to uncover the profile of emotional problems of academically outstanding students in the context of social interaction. The method used was qualitative descriptive by involving two key informants and four additional informants, namely a homeroom teacher, a counseling guidance teacher, and two peers (male and female). Data was collected through interviews, then analyzed by data reduction techniques, data presentation, and conclusion drawn. The results of the study show that some students have difficulty understanding themselves, especially in managing emotions and openness to sharing feelings. Negative emotions tend to be suppressed because of the difference between the feelings felt and the attitudes displayed. This condition creates communication barriers and potential conflicts with peers. Although academic achievement can increase confidence and courage to interact, emotional control is still an aspect that needs to be strengthened. Therefore, it is recommended that schools provide emotional skills development programs through training, group counseling, and activities that encourage openness, so that students' social interaction and self-understanding can be more optimal.